Fungal and bacterial diseases of cardamom (Elettaria cardamomum Maton) and their management - BHAI, JOSEPH THOMAS, R SUSEELA (Journal of Spices and Aromatic Crops, 1995)
Small cardamom (Elettaria cardamomum) is susceptible to a number of diseases due to fungi, bacteria and viruses. Twenty six different types of diseases have been reported of which only a few have been considered as major causing severe crop losses. The major diseases of fungal origin are ’azhukal’ (capsule rot) caused by Phytophthora meadii, rhizome rot (clump rot) and seedling rot (damping ofD caused by Phythium vexans, leaf blight caused by Phytophthora meadii, leaf blotch caused by Phaeodactylium alpiniae and leaf spots by Eercospora sp., and Sphaceloma cardamomi, leaf rust by Phakospora elettariae, brown spot by Colletotrichum gloeosporioides etc. Most of the diseases occur during the South West monsoon period where heavy rain coupled with high relative humidity predisposes the plant to infection. Since the occurrence and spread of diseases are correlated to weather conditions, integrated disease management strategy adopting cultural, chemical and biological control methods are highly suitable to save the crop from heavy losses.